Analisis Miskonsepsi Siswa Pada Pokok Bahasan Enzim dengan Menggunakan Tes Diagnostik Pilihan Ganda Beralasan - Fitrahayu; Muh. Khalifah Mustami; Jamilah (Al-AHYA: Jurnal Pendidikan Biologi, 2022)
The misconception is the inability to connect concepts to solve the problem correctly. This research was a case study that aimed to reveal the misconceptions of class XII students at SMA Negeri 2 Binamu Jeneponto on the enzyme subject. The instrument used was an open-ended multiple-choice diagnostic test with 15 questions regarding enzymes. Each test item consists of questions with four possible answers. Combining the students' answer selections and their justifications to create an answer statement that was similar to the response to the description question was the method used to analyze the answers to reasoned multiple-choice tests. The research analysis unit consisted of 26 class XII students. It was found that 17% of students experienced misconceptions about the enzyme subject. Students who have fewer misconceptions than students who do not understand the concept are equal to 43%. This study concludes that students have more partial misconceptions than complete misconceptions.